Ethics and Responsibility in Pharmaceutical Practice: Facing Moral Dilemmas in the Modern Era - Imam Jayanto; Untung Gunawan; Moh. Yaqya (Journal of Pharmacopoeia, 2024)
Pharmacy practice plays a crucial role in the modern healthcare system, providing access to safe and effective medicines for the public. However, in carrying out their profession, pharmacists are often faced with complex moral dilemmas. The modern era, with technological advances and commercial pressures, further complicates ethical decision-making. This article aims to examine ethical responsibilities in pharmacy practice and how pharmacists deal with conflicts of interest between economic gain and patient interests. Using a Systematic Literature Review (SLR) approach, this study identifies the main challenges faced by pharmacists in maintaining professional integrity while meeting regulatory demands and social expectations. The results suggest that pharmacists must adopt a balanced, value-based approach, where priority is given to patient welfare without neglecting the business aspects that are an integral part of healthcare. The discussion also explains the importance of developing ethical guidelines that are adaptive and relevant to the challenges of the digital era. The conclusion of this study is that a collaborative approach between government, professional organizations, and educational institutions can help create a stronger framework to support pharmacists in dealing with moral dilemmas in the workplace.